Black Raspberries Enhance Natural Killer Cell Infiltration into the Colon and Suppress the Progression of Colorectal Cancer - Pan, Pan; Kang, Siwen; Wang, Youwei; Liu, Ka; Oshima, Kiyoko; Huang, Yi-Wen; Zhang, Jianying; Yearsley, Martha; Yu, Jianhua; Wang, Li-Shu (Frontiers in Immunology, 2017)
Natural killer (NK) cells are an essential component of innate immunity against cancer development. Many studies have been conducted to evaluate immune-modulating effects using dietary compounds. Our laboratory has been investigating the chemopreventive potential of black raspberries (BRBs) and previously demonstrated their beneficial modulation of genetic and epigenetic biomarkers in patients with colorectal cancer (CRC). The current study investigated their potential on modulating NK cells. To avoid the excessive inflammation caused by the dextran sulfate sodium (DSS) treatment that leads to colitis, we treated the mice with overnight DSS so that it would slightly irritate the colon but still promote colon carcinogenesis with 100% incidence in both the ApcMin/+ mice and azoxymethane (AOM)-treated mice. A significant decrease of tissue-infiltrating NK cells along the progression of microadenoma-to-adenoma and adenoma-to-adenocarcinoma was observed in the ApcMin/+/DSS and AOM/DSS mice, respectively. Depletion of NK cells significantly promoted the development of CRC, suggesting a critical role of NK cells in combating CRC progression. BRBs significantly suppressed the CRC progression and increased the number of tissue-infiltrating NK cells in both mouse models. Moreover, we further determined BRBs’ effects on NK cells in the human biopsy specimens collected from our previously completed clinical trial, in which CRC patients consumed BRBs for an average of 4 weeks during a pre-surgical window. We observed an increased number and an enhanced cytotoxicity of NK cells by BRB intervention. The current study provides evidence that BRBs have the potential to enhance the tumor immunesurveillance of NK cells that can be beneficial in the setting of CRC prevention and treatment.